PESAT GALAT BIT PADA SANDI LOW DENSITY PARITY CHECK DENGAN HARD DECODING DAN SANDI BOSE-CHAUDHURI-HOCQUENGHEM - , FAVIAN DWI VANIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bose-Chaudhuri-Hocquenghem (BCH) codes and Low Density Parity Check (LDPC) are channel coding techniques which have the excellent ability to correct error in large number of bits. BCH is commonly used in digital devices such as CD, DVD, SSD, etc. BCH and LDPC are also used in the pair, for example DVB-T2 and DVB-S2.. This research aims to check the error correction capability of each code by simulation in digital communication systems with Binary Phase Shift Keying (BPSK) in Additive White Gaussian Noise (AWGN) channel. Simulation is carried out by changing the parameters of the Energy per Bit to Noise Power Ratio (Eb/N0). Based on the research result, BCH code shows better performance for correcting errors in AWGN channel than LDPC code. For the same code rate, BCH code is able to correct the error perfectly up to 1023 bits long code word. On other hand, up to Eb/N0 as high as 20 dB, the LDPC doesnât indicate ability to correct the errors.